2012
DOI: 10.1111/j.1553-2712.2012.01449.x
|View full text |Cite
|
Sign up to set email alerts
|

Survivors of Torture: Prevalence in an Urban Emergency Department

Abstract: Objectives: Torture has been documented in 132 countries, and approximately 400,000 survivors of torture reside in the United States. It is unknown if torture survivors seek medical care in emergency departments (EDs). The authors set out to estimate the prevalence of survivors of torture presenting to an urban ED.Methods: A cross-sectional survey of ED patients was performed by convenience sampling from October 2008 to September 2009 in a large urban teaching hospital in New York City. ED patients not of a vu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 19 publications
1
29
0
Order By: Relevance
“…Notably, 82% of the HRC cohort reported episodes of torture and/or human rights abuses; prevalence estimates of torture history vary from 6.6% at an urban primary care clinic to 11.5% in an urban emergency department cohort, and often go unreported [ 20 - 21 ]. Furthermore, the asylum-seekers’ legal affidavits reveal a wide variety of types of abuse suffered including persecution of marginalized political sects in Ethiopia, gang violence in Honduras and El Salvador, and sexual assault in Haiti and the Bahamas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, 82% of the HRC cohort reported episodes of torture and/or human rights abuses; prevalence estimates of torture history vary from 6.6% at an urban primary care clinic to 11.5% in an urban emergency department cohort, and often go unreported [ 20 - 21 ]. Furthermore, the asylum-seekers’ legal affidavits reveal a wide variety of types of abuse suffered including persecution of marginalized political sects in Ethiopia, gang violence in Honduras and El Salvador, and sexual assault in Haiti and the Bahamas.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the HRC cohort's prevalences of these mental health conditions are much higher than estimates for the general South Florida population (8.4% PTSD and 11.6% MDD) or United States (3.5% PTSD and 6.7% MDD) populations (see Figure 1) [18][19]. Notably, 82% of the HRC cohort reported episodes of torture and/or human rights abuses; prevalence estimates of torture history vary from 6.6% at an urban primary care clinic to 11.5% in an urban emergency department cohort, and often go unreported [20][21]. Furthermore, the asylum-seekers' legal affidavits reveal a wide variety of types of abuse suffered including persecution of marginalized political sects in Ethiopia, gang violence in Honduras and El Salvador, and sexual assault in Haiti and the Bahamas.…”
Section: New Contributions To the Literaturementioning
confidence: 99%
“…A consensus on torture prevalence levels in host countries, such as the ones derived from meetings of technical experts in the field is lacking. Several studies support prevalence levels of victims of torture between 5 and 35 % among refugees [46,48,49]. In Switzerland, Wicker found a prevalence rate of 30 % for torture survivors among recognised refugees [50].…”
Section: Proposed Ways Of Improvement: What Prevalencementioning
confidence: 99%
“…Presently, it affects millions of people in about 112 countries according to Amnesty International [9]. In some population groups (prisoners, refugees, or even patients in health-care services), prevalence levels can be high, yet vary widely according to the literature [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In one study of a New York City emergency department, more than threequarters of self-reported survivors of torture had never been asked by a physician about this crucial aspect of their history. 6 Seeking out foundational training in trauma-informed care-that is, best practices in interacting with survivors of diverse traumas-and learning to document human rights abuses as described in the United Nations' Istanbul Protocol is a first step you can take towards both aiding asylum seekers and augmenting our standard clinical acumen.…”
mentioning
confidence: 99%